Implementation Guide for Container-Grown Plant Interim Measure - Thomas H. Yeager (EDIS)
The purpose of this guide is to provide detailed information for use by greenhouse and nursery operators conducting specific fertilization and irrigation management practices to establish a waiver of liability for recovery costs resulting from nitrate contamination of ground water. This waiver is facilitated by the 1994 legislation (Chapter 576.045, F.S.) that provided for interim measures. Even though this publication was written specifically to help nursery operators implement fertilization and irrigation practices for the management of nitrate nitrogen, the concepts and principles are applicable to other nutrients, such as phosphorus, and potential groundwater contaminants. This document is ENH895, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 17, 2003.